Developing Spiritual Education: Solutions to Realize People Winning in the Free Market Era - Hartono, Djoko (http://jagadalimussirry.com/, 2020)
This research aims to find out ways and methods that can be done so that the spiritual development of education can be a solution to realize Indonesian society ready to compete in the free market era. This type of research is library research or library research that is designed through a qualitative approach using descriptive methods. Researchers as the main instrument in critically and in-depth study of relevant library materials. The results of the study pointed to k 's spiritual development can be used as a solution in creating a society ready to compete in a free market .